Адміністративно-правовий статус керівника районного відділу ОВС України : автореферат дисертації - Корнєєв, В. В.; Kornieiev, V. V. (Харків : Харківський національний університет внутрішніх справ, 2015)
Дисертація присвячена розгляду особливостей адміністративноправового статусу керівника районного відділу органів внутрішніх справ України. Визначаються поняття та види керівників органів внутрішніх справ, уточнюються їх значення та місце в системі ОВС України. Узагальнюються особисті якості керівника районного відділу ОВС України. Розмежовуються правовідносини, які виникають за участю керівника районного відділу в системі ОВС України. Визначаються особливості адміністративного законодавства в системі правового регулювання діяльності керівника районного відділу органів внутрішніх справ. Визначаються елементи адміністративно-правового статусу керівника районного відділу ОВС України. Формулюються пропозиції та рекомендації щодо вдосконалення адміністративного законодавства, яке регламентує правовий статус керівника районного відділу органів внутрішніх справ України.

The thesis is devoted to the peculiarities of administrative and legal status of the head of a district police station of Internal Affairs Agencies of Ukraine. The concept and types of the heads of internal affairs agencies are determined; their significance and place in the system of Internal Affairs Agencies of Ukraine are clarified. Personal qualities of the head of a district police station of Internal Affairs Agencies of Ukraine are summarized. Legal relations that arise involving the head of a district police station in the system of Internal Affairs Agencies of Ukraine are delineated. Features of administrative legislation in the system of legal regulation of the activity of the head of a district police station of internal affairs agencies are determined. Elements of administrative and legal status of the head of a district police station of Internal Affairs Agencies of Ukraine are characterized. Propositions and recommendations for improving administrative legislation that regulatesthe legal status of the head of a district police station of Internal Affairs Agencies of Ukraine are formulated.

Диссертация посвящена исследованию административно-правового статуса руководителя районного отдела органов внутренних дел Украины. Сформулированы критерии для классификации руководителей в системе органов внутренних дел. Раскрыты особенности и значение деятельности руководителей в системе ОВД. Охарактеризованы личные качества руководителя как факторы обеспечения эффективности управления служебной деятельностью на местном уровне. Разграничены правоотношения, которые возникают при участии руководителя районного отдела в системе органов внутренних дел. Особое внимание уделено вопросам правового регулирования деятельности руководителя районного отдела ОВД и определено место в нем административного законодательства. Раскрыто содержание и структура административно-правового статуса руководителя районного отдела ОВД, дана характеристика каждого элемента.
Автореферат дисертації на здобуття наукового ступеня кандидата юридичних наук
Administrative and Legal Status of the Head of a District Police Station of Internal Affairs Agencies of Ukraine
Keywords: Автореферати дисертацій. Abstracts of Theses. Авторефераты диссертаций; 12.00.07; Україна; органи внутрішніх справ; internal affairs agencies; органы внутренних дел; керівник; head; руководитель; районний відділ; district department; районный отдел; адміністративно-правовий статус; administrative and legal status; административно-правовой статус; правове регулювання; legal regulation; правовое регулирование